Colorful parade from the island of God - Ida Ayu Agung Adnyawati (Bali Tourism Board, 2018)
In expressing their gratitude to the creator, Balinese believes, they should always provide their best. One of the examples is by doing Mapeed. Mapeed aims to show their appreciation to Ida Sang Hyang Widhi Wasa, or God Almighty. The participant or peed mainly carried out by the women. While for the men, they are assigned as the banner carrier, Sekaa Gong, Sekaa Santhi, and Pecalang. Balinese female; from children, adolescents, to adults would march in line carrying Gebogan. Before the procession begins, members of the traditional village council conduct a Paruman or a meeting. The elder determines which Banjar or community groups, would have their turn to present their ayahan or community service on occasion. Since ancient time, Balinese has been practicing mapeed as part of yadnya. The existence of mapeed is proof of how Balinese respect heritage that has been passed on them by their ancestor. The practice if it is carefully observed is full of value about solidarity, togetherness, and faith. Although the rise of modernization in Bali, apparently do not stop the folk practice the tradition. Moreover, the parade always captivates people around it, to behold as they march gracefully crossing the hustle bustle face of Bali’s today.